2020
DOI: 10.4088/jcp.19r13106
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 Fatty Acid Supplementation for Perinatal Depression

Abstract: Objective: Several randomized controlled trials (RCTs) investigated omega-3 polyunsaturated fatty acids (PUFAs) (ie, fish oil) in perinatal depression, but their efficacy remains unclear. We performed a meta-analysis of RCTs on omega-3 PUFAs for perinatal depression, comparing a priori defined subgroups: pregnant women vs postpartum women and prevention vs treatment of perinatal depression. Methods: We searched Web of Science, Embase, PsycINFO, and the Cochrane Library, combining omega-3 PUFAs and perinatal de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…At present, the physiological causes of PPD are mainly neuroendocrine factors, which are considered to be abnormal central neurotransmitter metabolism and changes in related receptor functions, such as 5-hydroxytryptamine (5-HT), dopamine, and norepinephrine. In recent years, studies have focused on W-3 unsaturated fatty acids, such as eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) (Markhus et al, 2015;Hsu et al, 2018;Mocking et al, 2020). Pawluski et al (2017) also found through functional magnetic resonance imaging (fMRI) that the connections between the amygdala, anterior cingulate gyrus, dorsolateral prefrontal cortex, and hippocampus in PPD patients are significantly reduced, and the activity of the left amygdala is significantly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the physiological causes of PPD are mainly neuroendocrine factors, which are considered to be abnormal central neurotransmitter metabolism and changes in related receptor functions, such as 5-hydroxytryptamine (5-HT), dopamine, and norepinephrine. In recent years, studies have focused on W-3 unsaturated fatty acids, such as eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) (Markhus et al, 2015;Hsu et al, 2018;Mocking et al, 2020). Pawluski et al (2017) also found through functional magnetic resonance imaging (fMRI) that the connections between the amygdala, anterior cingulate gyrus, dorsolateral prefrontal cortex, and hippocampus in PPD patients are significantly reduced, and the activity of the left amygdala is significantly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Moderate intake of n-3 PUFAs (approximately 0.5-1 g/day) was significantly associated with a lower prevalence of depression 31) . EPA may exert anti-inflammatory benefits in women with perinatal depression 32) . The treatment efficacy of n-3 PUFA supplementation depends on the proportion and dose of EPA and DHA 33) .…”
Section: N-3 Polyunsaturated Fatty Acidsmentioning
confidence: 99%
“…Rare: More serious injuries SAMe 8 Nausea, mild insomnia, dizziness, irritability, anxiety Vitamin D [1][2][3][4][5] Toxicity (uncommon), which may include weakness, fatigue, sleepiness, headache, dry mouth, metallic taste, loss of appetite, nausea, vomiting Probiotics [10][11][12] May trigger allergic reactions or cause mild stomach upset, diarrhea, flatulence, or bloating Mindfulness-based interventions 31,32 May negatively affect emotions, sensory perception, social interactions, sense of self Essential fatty acids [5][6][7] Accumulates in adipose tissue. In this context, omega-6 rich diets can increase oxidized low-density lipoprotein levels…”
Section: Low Riskmentioning
confidence: 99%
“…6 Furthermore, omega-3 fatty acids may be helpful as an add-on agent for postpartum depression. 7 Be aware that a diet rich in omega-6 greatly increases oxidized low-density lipoprotein levels in adipose tissue, potentially posing a cardiac risk factor. Clinicians need to be aware that self-prescribed use of essential fatty acids is common, and to ask about and monitor their patients' use of these agents.…”
mentioning
confidence: 99%